Pendampingan Digital Marketing dan Branding UMKM Achiera Bouquet - Lesa, Natasha Cristy; Pasaribu, Masdelina; Yosepha, Novia; Jannati, Nur; Rochma, Pradya Ingri Nabila; Christian, Iwan (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to optimize the development of MSMEs through the implementation of effective digital marketing and branding strategies. This activity was carried out on August 25 - September 28, 2024 through the participatory action research method. Among the mentoring activities are market analysis, digital content creation, social media management, and designing a stronger brand identity. The results of community service activities are that increasing brand recognition and product sales can be done through optimizing digital platforms. This mentoring can improve the ability of MSMEs to manage digital marketing and branding, thereby helping the Achiera Bouquet business grow.